Analysis of the influence of soft soil grouting on the metro tunnel based on field measurement. Issue 5 (10th June 2019) - Ding, Zhi; Zhang, Xiao; Yin, Xinsheng; Jiang, Jiqing
Abstract : Purpose: This paper aims to analyse the effect of soft soil grouting on the deformation of the closed shield tunnel with the measured data. Design/methodology/approach: Combining the measured data of vertical, horizontal and convergence deformation of the adjacent tunnel during the grouting construction in foundation pit engineering, the influence of grouting on metro tunnel in soft soil area is analyzed. Findings: The researches indicate that early grouting has the main effect on the horizontal displacement of the tunnel; Due to the disturbing effect of the uninterrupted grouting construction on the soil and the transfer pressure of the rheological soil to the bottom of the tunnel, the tunnel is obviously lifted; And the convergence deformation of the tunnel increases caused by the overburden pressure in the vertical direction, so that the tunnel appears the phenomenon of staggered seam, large opening of bolted joint, damaged segment even leakage of water. Originality/value: The study based on the field monitoring data is rarely reported, especially the topic about inadvertent grouting in soft soil area is likely to cause severe deformation of adjacent metro tunnel.